Examining Changes Trend of Fluoride Concentration in Groundwater Using Geo-Statistical Technique and Its Zoning in Geographic information system (GIS), Case Study: Drinking Water wells in Yazd-Ardakan Plain - razieh charkhkarzadeh; zahra derakhshan; mohammad miri; mohammad hasan ehramposh; mohammad hasan lotfi; vahid jafari nodoshan (Shahid Sadoughi University of Medical Sciences, 2015)
Background and Objective: Studies have shown that the presence of standard amount of fluoride in drinking water can prevent tooth decay. Meanwhile, higher concentration than permitted amount in drinking water causes bone disease and dental fluorosis. Given the importance of fluoride in drinking water and also GIS ability in spatial analysis of various factors in the groundwater, in this study the concentration of fluoride in the plain of Yazd-Ardakan has been investigated using two IDW (Inverse Distance Weighting) and Kriging models. Materials and Methods: In this study, the data on the water quality of underground water of Yazd Regional Water Company and the average annual fluoride in 2014 were used. The data were related to 76 rural wells and 107 urban wells in the studied area. The rate of fluoride in groundwater in rural and urban areas was compared to the standard amount in Iran and then was analyzed via Arc GIS software using IDW and Kriging interpolation methods. Results: The mean concentration of fluoride was 0.68 mg/l in rural areas and 0.7 mg/l in urban areas. With regard to the minimum and maximum concentrations of fluoride and standard deviation of 0.364, fluoride concentration fluctuations in rural areas were higher than urban areas. For both rural and urban areas Kriging interpolation method was more efficient than IDW method. Conclusion: The residents of southern districts of Yazd-Ardekan are more facing the shortage of fluoride in drinking water and the risk of tooth decay and necessary management should be done in these areas. Geo-statistical methods can greatly help understand environmental issues.